Outcomes for allogeneic stem cell transplantation in refractory mycosis fungoides and primary cutaneous gamma Delta T cell lymphomas. Issue 12 (14th October 2020) - Isufi, Iris; Seropian, Stuart; Gowda, Lohith; Wilson, Lynn D.; Roberts, Kenneth; Girardi, Michael; Perreault, Sarah; Foss, Francine
Abstract: We report results on 23 patients with cutaneous T cell lymphoma (7 primary cutaneous γδ T cell lymphoma [PCGDT], 16 mycosis fungoides/Sézary syndrome [MF/SS]) who underwent allogeneic stem cell transplantation. All pts had skin involvement, 14 had total skin electron beam before conditioning. Donors were 10/10 HLA matched related (13), 5/10 haploidentical (4), and matched unrelated (5) or mismatched unrelated (1). Thirteen were in a clinical complete remission at the time of transplant. The 100-day transplant related mortality for the MF/SS and PCGDT patients was 12% and 29%, respectively. At a median follow up of 5.5 years, the overall survival and disease-free survival for MF/SS patients was 75% and 64%, respectively, and 6 of 10 MF/SS pts in long term complete response had a partial response at the time of transplant. Of seven PCGDT patients, four of seven are alive at a median follow up of 5 years and three are disease-free.